Development of Hiccup in Male Patients Hospitalized in a Psychiatric Ward: Is it Specifically Related to the Aripiprazole-Benzodiazepine Combination?. Issue 2 (March 2016) - Caloro, Matteo; Pucci, Daniela; Calabrò, Giuseppa; de Pisa, Eleonora; Mancinelli, Iginia; Rosini, Enrico; Montebovi, Franco; De Filippis, Sergio; Telesforo, Carla Ludovica; Cuomo, Ilaria; Kotzalidis, Georgios D.; Girardi, Paolo
Abstract : Objectives: The aim of this study was to identify hiccup cases among patients hospitalized in a psychiatric ward and focus on their treatment, so to establish intervention risk. Methods: We reviewed records of 354 consecutively admitted patients during the year 2013 to identify hiccup cases. Results: Hiccup occurred in 7 patients on both aripiprazole and benzodiazepines and in one on delorazepam. No patient on aripiprazole alone developed hiccup. No patient on drugs other than aripiprazole or benzodiazepines developed hiccup. The symptom subsided in 3 cases upon discontinuing aripiprazole and in 5 cases after discontinuing the benzodiazepine (including the case on delorazepam alone); in 2 cases of persistent hiccup, the symptom resolved after adding the calcium channel blocker, pregabalin. All patients developing hiccup were male. There was a 70-fold increase in the risk for developing hiccup in the aripiprazole/benzodiazepine intake condition versus all other conditions, and it further increased if limiting to the male sex. Limitations: The retrospective nature of the study was its limitation. Conclusions: Hospitalized psychiatric patients on both aripiprazole and benzodiazepines may be at significant risk of hiccup. This clinical awareness could lead to antipsychotic and/or benzodiazepine discontinuation or switch or to the addition of calcium channel blocker inhibitors.